2018
DOI: 10.1111/bioe.12469
|View full text |Cite
|
Sign up to set email alerts
|

Positioning uterus transplantation as a ‘more ethical’ alternative to surrogacy: Exploring symmetries between uterus transplantation and surrogacy through analysis of a Swedish government white paper

Abstract: Within the ethics and science literature surrounding uterus transplantation (UTx), emphasis is often placed on the extent to which UTx might improve upon, or offer additional benefits when compared to, existing ‘treatment options’ for women with absolute uterine factor infertility, such as adoption and gestational surrogacy. Within this literature UTx is often positioned as superior to surrogacy because it can deliver things that surrogacy cannot (such as the experience of gestation). Yet, in addition to claim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 0 publications
0
16
0
2
Order By: Relevance
“…In many previous papers, UTx has been described as the only option to have a genetic link to the child when gestational surrogacy is prohibited. In addition, even when live donor UTx is performed, UTx is considered superior to surrogacy, since it is supposed to be a less morally problematic alternative to gestational surrogacy [15]. However, some authors are skeptical of the assumption that UTx is morally superior to gestational surrogacy [15].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In many previous papers, UTx has been described as the only option to have a genetic link to the child when gestational surrogacy is prohibited. In addition, even when live donor UTx is performed, UTx is considered superior to surrogacy, since it is supposed to be a less morally problematic alternative to gestational surrogacy [15]. However, some authors are skeptical of the assumption that UTx is morally superior to gestational surrogacy [15].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, even when live donor UTx is performed, UTx is considered superior to surrogacy, since it is supposed to be a less morally problematic alternative to gestational surrogacy [15]. However, some authors are skeptical of the assumption that UTx is morally superior to gestational surrogacy [15]. In addition, it has been reported that the perinatal risk during gestational surrogacy is not significantly different from that attributable to in vitro fertilization using fresh embryos [16, 17].…”
Section: Discussionmentioning
confidence: 99%
“…Besides, participants felt that surrogacy and adoption posed significant risks to their emotional well‐being . Morally speaking, using living donors in UTx is superior to altruistic surrogacy for being less fraught with ethical and regulatory difficulties and quandaries than surrogacy . In 2017, a small questionnaire study in China showed that 25.8% of Mayer–Rokitansky–Kuster–Hauser syndrome patients prefer to choose UTx to get a baby, while 19.3% choose gestational surrogacy .…”
Section: Why Utx In China?mentioning
confidence: 99%
“…19,22 Morally speaking, using living donors in UTx is superior to altruistic surrogacy for being less fraught with ethical and regulatory difficulties and quandaries than surrogacy. 23 In 2017, a small questionnaire study in China showed that 25.8% of Mayer-Rokitansky-Kuster-Hauser syndrome patients prefer to choose UTx to get a baby, while 19.3% choose gestational surrogacy. 24 At present, a large web-based survey regarding human UTx among the Chinese public, AUFI patients and Chinese healthcare providers is underway (unpublished data), and the results are expected to provide a reference for the ongoing clinical trials on human UTx in China.…”
Section: Why Utx In China?mentioning
confidence: 99%
“…For both living and deceased donation, there is a risk of uteri being obtained without sufficiently high-quality consent . For living donation, concerns center around the possibility of living related donors experiencing external pressures such as coercion or manipulation to donate from the recipient or other family members, 8 and that living unrelated donors may be offered incentives (financial or otherwise) that could constitute an autonomy-undermining inducement 31 . The design and implementation of robust consent procedures can reduce such risks, as in other donation contexts.…”
Section: Introductionmentioning
confidence: 99%